Social entrepreneurship : a skills approach - Durkin, Christopher, ....-; Gunn, Robert, ....- (Bristol : Policy Press, 2017)
The second edition of this popular book has been inspired by the increasing interest around social entrepreneurship scholarship and the practice of delivering innovative solutions to social issues. Although social enterprises generally remain small, the impact of social entrepreneurs is increasing globally, as all countries are endeavouring to respond to increasingly complex social problems and demands for welfare at a time of government cut backs. Additional chapters and international case studies explore new developments, such as the rise of the social investment market, the use of design thinking and the increasing importance of social impact measurement.
Keywords: Sociaal ondernemen